Developing the high performance practices to attain Organizational effectiveness - حمود العنزي, سعد علي; حسين, سمر عادل (Journal of Economics and Administrative Sciences, 2013)
Abstract         This current research aims to make theoretical frame for the thoughts and principle knowledge for high performance work system ،also trying to know the role that high performance work system practices which is (Effective staffing، comprehensive training، providing work career، and employee participation) play to enhance the  organization effectiveness ، although knowing the principles of high performance work system which is: (Shared Information، Knowledge Development Performance and Reward linkage Egalitarianism)and its effect on the organizations. As well as defining the special concept of High performance work system ، because its represent a very important part  in the organizations culture in the present time  and because these organization work in a very changeable environment ، as result for that the change leaders take on their own to redirect their organizations and shift their a tension from revenue monitoring towards customers monitoring ، and productivity increasing towards continues enhancing process ،and from achieving short term financial goals  towards employee satisfaction .This research also aims to clarify the relationship between HPWS and other HR variable and also discussed the component of HPWS which is bundle of desirable processers and applications which can be more activity when it works together.